The Relation between Cost Shifting and Segment Profitability in the Defense-Contracting Industry - McGowan, Annie S.; Vendrzyk, Valaria P. (The Accounting Review, 2002)
We test the conjecture from prior research that defense contractors' excess profitability in the 1980s stemmed from their ability to shift common overhead costs to government contracts that typically allow cost reimbursement or price renegotiation (Rogerson 1992; Thomas and Tung 1992; Lichtenberg 1992). Although we confirm prior evidence that defense contractors enjoyed abnormally high profitability on their government work in the 1984–1989 period (a period of relatively low competition for defense contracts), we find no evidence that this excess profitability is attributable to cost shifting. In addition, we find no evidence that the Top 100 defense contractors (firms that likely wield above-average market power) are able to use cost shifting to exploit a lack of competition in the industry. Our results suggest that, contrary to the conjectures in prior research, the unusually high profitability reported on government contracts in 1984–1989 is more likely attributable to nonaccounting explanations than to cost shifting.